A review of anticorrosive, superhydrophobic and self-healing properties of coating-composites as corrosion barriers on magnesium alloys: Recent advances, challenges and future directions - Babalola Aisosa Oni; Olusegun Stanley Tomomewo; Solomon Evro; Andrew N. Misiani; Samuel Eshorame Sanni (Journal of Magnesium and Alloys, 2025)
Magnesium and its alloys have gained relevance for their light-weight combined with a high value of strength-to-weight ratio, which makes them useful in fields such as aerospace, automotive as well as biomedical engineering. Unfortunately, the poor corrosion resistance of Mg-alloys limits their wide acceptance. Advanced composite coatings which are self-healing, superhydrophobic anti corrosive, and wear resistant are new synthetic materials for abating these challenges. The superimposed superhydrophobic surfaces help in minimizing their water contact, thus slowing down the electrochemical reactions on the surface of the alloys, while their self-healing characteristics autonomously aid in the repair of any induced micro-crack, defect or damage towards ensuring the metal’s long-term protection. In addition, the integration of wear-resistant materials further improves the durability of coatings under mechanical stress. The most recent research efforts have been directed towards the preparation of multifunctional composites, with an emphasis on nanomaterials, functional polymers, and state-of-the-art fabrication techniques in order to take advantage of their synergistic effects. Some of the methods that have so far exhibited promising potentials in fabricating these materials include the sol-gel method, layer-by-layer assembly, and plasma treatments. However, most of the fabricated products are still faced with significant challenges ranging from long-term stability to homogeneous adhesion of the coatings and their scalability for industrial applications. This review discusses the recent progress and the relationship between corrosion inhibition and self-healing efficiencies of wear resistant polymer nanocomposite coatings. Some challenges related to optimizing coating performance were also discussed. In addition, future directions ranging from the consideration of bioinspired designs, novel hybrid nanocomposite materials, and environmentally sustainable solutions integrated with smart protective coatings were also proposed as new wave technologies that can potentially revolutionize the corrosion protection offered by Mg alloys while opening up prospects for improved performance and sustainability.